Penggunaan Media Tumbuh-Tumbuhan dalam Peningkatan Kreativitas Menggambar Anak Usia 5-6 Tahun di Desa Ongko Tahun 2020 - Reni Hidayati; I Made Suwasa Astawa; Muazar Habibi; Baik Nilawati Astini (Indonesian Publication Center, 2021)
This research was motivated by the results of observations made during the Covid-19 period while still paying attention to the prevailing health protocols in Ongko Village, it was found that creativity in drawing children aged 5-6 years only used paper and colored pencils. So that children become less creative in developing their imagination when drawing. Based on this background, the problem formulated in this study is How to Use Plant Media in Increasing Creativity in Drawing for 5-6 Years Old Children in Ongko Village in 2020? This is to find out the use of plant media in increasing creativity in drawing children aged 5-6 years in Ongko Village in 2020. This type of research is qualitative field research. The number of samples in this study were 3 children. Data collection activities used is the activity of observation, interviews, and documentation, while the data analysis used is descriptive qualitative analysis. The results showed that in observation I, the lowest percentage obtained by children was 51% of children developing according to expectations (BSH), while the highest percentage obtained by children was 67% of children developing according to expectations (BSH). In second observation, the lowest percentage obtained by children was 76% of children developing very well (BSB), while the highest percentage obtained by children was 85% of children developing very well (BSB). So it can be concluded that the use of plant media can increase children's creativity in drawing by utilizing the existing plants around children such as croton plants, tamarind leaves, and so on. This will provide a different experience for children, especially in developing their creativity in drawing.